Justiça, profissionalismo e política: o Supremo Tribunal Federal e o controle da constitucionalidade das leis no Brasil (1988-2003) - Oliveira, Fabiana Luci de (Universidade Federal de São Carlos, 2006)
This research focuses on the interactions among law, professionalism and politics in Brazil. The primary intent is to understand the judicial behavior of Brazil s Supreme Court in the exercise of judicial review, from the promulgation of the 1988 s Constitution to march, 2003. We analyzed Justices votes in decisions regarding the constitutionality of laws (ADINS) in search of the factors that most influenced the Court s decisions. We analyzed these decisions both, quantitatively and qualitatively, in search of a) factors that determine justices votes and the court decisions; b) differences in vote corresponding to the career of each member of the Court, c) the justices profile and the way they clustered to vote, and d) the Justices attitudes as either Constitution interpreters or reproducers of legal texts. The theoretical and methodological approaches that guide this discussion of the interaction of the juridical (professional) and the political action of the Court were derived from the sociology of professions and the judicial politics approaches. From the results we can conclude that law and politics are extremely related in the decision making process of Brazil s Supreme Court, and professionalism works in this relationship as a way of distinction, a legitimacy source of an actor that has great political power but lacks electoral support.
Keywords: Sociologia política; Profissões jurídicas; Supremo Tribunal Federal; Direito; Revisão judicial; CIENCIAS HUMANAS::SOCIOLOGIA